THE EFFECT OF ORGANIZATIONAL COMMITMENT, WORK MOTIVATION AND COMPENSATION ON JOB SATISFACTION AT DARUL QUR'AN ISLAMIC BOARDING SCHOOL MULIA BOGOR - Yenni Cahyani (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
This study aims to determine the effect of organizational commitment, work motivation and work compensation on job satisfaction of employees of the Integrated Islamic Boarding School Darul Qur'an Mulia Bogor. This research is a quantitative analysis study using simple and multiple linear regression analysis. The type of data used in this study is primary data. The type of primary data in this study is in the form of a questionnaire given to 100 respondents. The data obtained is then processed using the help of the SPSS For Windows 24 Program. The analysis shows organizational commitment has a positive and significant effect on job satisfaction. Motivation has a positive and significant effect on job satisfaction. Compensation has a positive and significant effect on job satisfaction. Simultaneously, organizational commitment, motivation and compensation simultaneously influence job satisfaction.